Pengaruh Motivasi Kerja, Komitmen Organisasi Dan Kompensasi Terhadap Kinerja Pegawai Dengan Kepuasan Kerja Sebagai Variabel Moderating (Studi Kasus Pada Dinas Perpustakaan dan Arsip Kab. Labuhan Batu) - Sari Munthe, Siti Maya (Universitas Labuhanbatu, 2021)
The library is a work unit of an agency or institution that manages library materials, these materials can be in the form of books or not (non book material) which is compiled scientifically and systematically with certain rules so that it is useful as a source of information for those in need. In the library the most basic and main task is to provide services to users. For that as one of the Library Information Center is required to be able to provide better service and quality and appropriate, so as to attract the attention of all elements of membership pemustaka who have different striped background both from the status of students, students, employees and ASN even children (potential users). Library is one of the facilities that continuously provide information and cultural preservation facilities that have a role in meeting the needs of education, research and development of science. This study aims to determine and analyze the effect of work motivation, organizational commitment, and compensation on employee performance with job satisfaction as a moderate variable. The results showed that work motivation has a positive and significant effect on employee performance with a value of T1 count of 5.599 > ttable of 1.677 with a significance of 0.000 < 0.05. Organizational commitment has a positive and significant effect on employee performance with T2 count value of 2.140 > ttable of 1.677 with significance of 0.038 < 0.05. Compensation positive and significant effect on employee performance with T3 count value of 2.220 > ttable of 1.677 with significance of 0.032 < 0.05. Work motivation, organizational commitment and compensation simultaneously have a positive and significant effect on employee performance with a value of F table = 3.19 while F count 90.374 so Ftable > Fhitung, with a significance level of 0.000 > 0.05 at the level of confidence 95% and Alpha 5%. Job satisfaction is proven to moderate the relationship between work motivation, organizational commitment and compensation for employee performance.Â